A Study on the Effect of Hardware Trojans in the Performance of Network on Chip Architectures - Philomina, Josna (2021 8th International Conference on Smart Computing and Communications (ICSCC), 2021)
Network on chip (NoC) is the communication infrastructure used in multicores which has been subject to a surfeit of security threats like degrading the system performance, changing the system functionality or leaking sensitive information. Because of the globalization of the advanced semiconductor industry, many third-party venders take part in the hardware design of system. As a result, a malicious circuit, called Hardware Trojans (HT) can be added anywhere into the NoC design and thus making the hardware untrusted. In this paper, a detailed study on the taxonomy of hardware trojans, its detection and prevention mechanisms are presented. Two case studies on HT-assisted Denial of service attacks and its analysis in the performance of network on Chip architecture is also presented in this paper.